Pharmacological Evaluation of the SCID T Cell Transfer Model of Colitis: As a Model of Crohn's Disease - Thomas Lindebo Holm; Steen Seier Poulsen; Helle Markholst; Stine Reedtz-Runge (International Journal of Inflammation)
Animal models are important tools in the development of new drug candidates against the inflammatory bowel diseases (IBDs) Crohn's disease and ulcerative colitis. In order to increase the translational value of these models, it is important to increase knowledge relating to standard drugs. Using the SCID adoptive transfer colitis model, we have evaluated the effect of currently used IBD drugs and IBD drug candidates, that is, anti-TNF-α, TNFR-Fc, anti-IL-12p40, anti-IL-6, CTLA4-Ig, anti-α4β7 integrin, enrofloxacin/metronidazole, and cyclosporine. We found that anti-TNF-α, antibiotics, anti-IL-12p40, anti-α4β7 integrin, CTLA4-Ig, and anti-IL-6 effectively prevented onset of colitis, whereas TNFR-Fc and cyclosporine did not. In intervention studies, antibiotics, anti-IL-12p40, and CTLA4-Ig induced remission, whereas the other compounds did not. The data suggest that the adoptive transfer model and the inflammatory bowel diseases have some main inflammatory pathways in common. The finding that some well-established IBD therapeutics do not have any effect in the model highlights important differences between the experimental model and the human disease.